The Role of the Indonesian Constitutional Court for An Effective Economic, Social and Cultural Rights Adjudication - Triyana, Heribertus Jaka (Constitutional Review, 2015)
The Indonesian Constitutional Court has played important roles and functions to protect and fulfill human rights in the Indonesian legal system including the economic, social and cultural rights through its legal power of Â judicial review. Â  It affirms that the ecosoc rights are legal justiciable rights and they are parts of constitutional mandates. It means that decision on judicial reviews require State to behave in accordance to legal thresholds decided by the Court. Undoubtedly, compliance to the decisions will reveal undeniable facts for fulfilment of state conduct. However, it seems that there are still many considerations, emphasis and excuse to somehow reduce or ignore threshold of application of the Court decisions. Complexity of actors, institutions, authorities, level of implementation, and orientation of particular policies, programs, actions and funds reduces the thresholds.